The Comparison between Interpreting and Translation Process - Suryasa, I Wayan (International Research Journal of Management, IT & Social Sciences, 2016)
The research was intended to identify the differences between translating and interpreting process, in order to explain the similarities of translating and interpreting process, and describing how the process between translating and interpreting process. There were two main theories adopted in this study. The theory of translation by Nida (1974) and interpreting theory by Pohhacker (2004). Nidaâs and Pohhcakerâs theories were used to find out the answer of problem in this study. They were also some supporting theories concerning the translation and interpreting. âMeaning Based Translationâ by Larson (1998) and some other theory were used along discuss about the differences and similarities of translating process and interpreting process in this study.